2005
DOI: 10.1038/sj.ejhg.5201505
|View full text |Cite
|
Sign up to set email alerts
|

Replication of IGF2-INS-TH*5 haplotype effect on obesity in older men and study of related phenotypes

Abstract: Interindividual variation of the IGF2-INS-TH region influences risk of a variety of diseases and complex traits. Previous studies identified a haplotype (designated IGF2-INS-TH*5 and tagged by allele A of IGF2 ApaI, allele 9 of TH01 and class I alleles of INS VNTR) associated with low body mass index (BMI) in a cohort of UK men. We aimed here both to study whether previous findings relating *5 with weight are replicated in a different cohort of men (East Hertfordshire) characterised in more phenotypic detail a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…A haplotype including the minor (A) alleles of the IGF2 ApaI (rs680) polymorphism and microsatellites in the INS and TH01 genes was associated with a reduction in body mass index in Caucasian males [ 23 ] . A replication study suggested that this association was specifi c to male subjects and that reduction in BMI was related to a decrease in visceral obesity [ 24 ] . The ApaI AA genotype has also previously been associated with a decrease in circulating IGF-II and higher body weight in Caucasian males [ 25 ] .…”
Section: Discussionmentioning
confidence: 97%
“…A haplotype including the minor (A) alleles of the IGF2 ApaI (rs680) polymorphism and microsatellites in the INS and TH01 genes was associated with a reduction in body mass index in Caucasian males [ 23 ] . A replication study suggested that this association was specifi c to male subjects and that reduction in BMI was related to a decrease in visceral obesity [ 24 ] . The ApaI AA genotype has also previously been associated with a decrease in circulating IGF-II and higher body weight in Caucasian males [ 25 ] .…”
Section: Discussionmentioning
confidence: 97%
“…*5 was also associated with related subphenotypes (plasma insulin and glucose levels at baseline and after a GTT), supporting that the weight-lowering eVect found for *5 has a biological basis Rodríguez et al (2006a) Other species…”
Section: Igf2-ins-thmentioning
confidence: 64%
“…There is evidence in the literature suggesting that there may be diVerences between men and women in the genetic factors that inXuence variation in metabolic syndrome risk traits (Poulsen et al 2001;Schousboe et al 2003). Interestingly, most metabolic eVects that our group has seen in the growth hormone and growth factor pathways are sex-speciWc (Rodríguez et al 2004(Rodríguez et al , 2006aDay et al 2004a). Indeed, there are considerable diVerences between men and women in the diurnal proWles of GH pulsatility from the brain (van den et al 1996;Roelfsema et al 2002;Day et al 2004a).…”
Section: The Gh-igfs Pathway In Relation To Metabolic Human Diseases mentioning
confidence: 87%
See 1 more Smart Citation
“…There are six well-characterized mammalian IGF binding proteins, designated IGFBP-1 to IGFBP-6 [2][3][4][5][6]. They are proteins of 216-289 residues and consist of three distinct domains of approximately equal size [7].…”
Section: Introductionmentioning
confidence: 99%